Applicability evaluation of cast-in-place bored pile in permafrost regions based on a temperature-tracking concrete hydration model. (25th February 2019) - Gao, Qiang; Wen, Zhi; Ming, Feng; Liu, Jiankun; Zhang, Mingli; Wei, Yanjing
Highlights: A temperature-tracking concrete hydration model that considering effect of the permafrost curing environment is developed. Both quality of cast-in-place bored pile and engineering schedule in permafrost regions were considered in this study. Applicability range of cast-in-place bored piles can be expanded by increasing the molding temperature and the pile diameter. Abstract: In recent years, cast-in-place bored piles have been widely used in engineering constructions. However, the applicability of bored pile was constricted by the loss of concrete strength in the cold curing environment of permafrost. A temperature-tracking concrete hydration model was developed to clarify the refreezing process of the bored pile. Based on an initial refreezing time (IRT) on the pile side of at least 30 days, the applicability of cast-in-place bored pile in permafrost regions was discussed. The results show that the IRT increases with the increasing of the mean annual ground temperature (MAGT), the ice content of frozen soil, the molding temperature of concrete, and the pile diameter. The applicability of the bored pile can be expanded by increasing the diameter of the bored pile as well as the molding temperature. Particularly, the influence of diameter is more obvious than that of the molding temperature. The simulations indicate that the bored pile is not recommended to be adopted in perennially cryotic ground where the MAGT is lower than −3.5 °C. The IRT should be adjusted to guarantee both pile quality and schedule.